Formulation, Characterisation And In Vitro Skin Irritation Studies Of Jasminum Officinale And Anthemis Nobilis Essential Oil Nanoemulsion For Aedes AEGYPTI Repellent Activity - Muttiah, Nithya Niranjini (2019)
Mosquitoes are important vectors responsible for the transmission of many pathogens that cause major human morbidity and mortality. Aedes aegypti is the main species engaged in the transmission of dengue fever. Natural repellents such as essential oils may provide a means of protection from mosquito bites that are safer and more pleasant to use. However, their effectiveness decreases relatively fast over time due to high volatility. Nanoemulsion formulation enables to control the volatility of essential oil and thereby extends the duration of repellency. Therefore, oil-in-water nanoemulsion containing the mixture of Jasminum officinale and Anthemis nobilis essential oils were formulated via ultrasonication, and characterised with respect to droplet size, polydispersity index (PDI), zeta potential and storage stability. Gas chromatography-mass spectrometry (GC-MS) analysis revealed that oxygenated monoterpenes and diterpenes constituted 31.14% and 21.20% of J. officinale, respectively. For A. nobilis, oxygenated monoterpenes accounted for 84.79% of the compounds identified. The combination of J. officinale and A. nobilis in a 1:1 ratio exhibited significantly (p < 0.05) higher repellency against Ae. aegypti using a rat model for 120 min than the individual oils. The droplet size of nanoemulsions; nJC1, nJC2 and nJC3 were 264.23, 291.43 and 351.37 nm, respectively. The zeta potential and PDI of the nanoemulsions were -32.77 to -46.93 mV and 0.232 to 0.264, respectively.